DUE TO ANTHROPOGENIC CHANGES IN THE ECOLOGICAL CONDITIONS, THE NEGATIVITY THAT OCCURS IN THE AEROBIC CAPACITY OF STUDENTS. - G.N. Ernazarov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In Vodil and Kuvasoi, the physical and work abilities, maximum breathing with oxygen, and heart activity of students with different environmental conditions were studied. It was found that the ability of a boy living in anthropogenic conditions is lower, pupil fatigue is in Kuvasoi.